Accessing the medical devices market in Egypt and Saudi Arabia: a systematic review of policies and regulations. (2nd July 2016) - Gad, Mohamed; Kriza, Christine; Fidler, Armin; Kolominsky-Rabas, Peter
ABSTRACT: Introduction: Despite the significant medical devices market size in Egypt and Saudi Arabia, information regarding policies and regulations for medical devices market access is highly deficient. Areas covered: The aim of this paper is to provide a systematic review on market access policies and regulations in both countries, to allow safe and timely access to medical technology. The following databases were searched: PubMed, Science Direct, Scopus, and Al Manhal Arabic database. Additionally, the web portals of regulatory authorities of both countries were searched. There are 34 records included in the qualitative synthesis of this review. Expert commentary: Main findings include; adopted regulatory framework from reference countries, and interim main regulatory documents, In conclusion, the market access schemes are relatively structured. However, some recommendations are put forward to navigate towards a more comprehensive policy framework in both countries.